Complete Genome Sequencing of Mycobacterium bovis SP38 and Comparative Genomics of Mycobacterium bovis and M. tuberculosis Strains - Zimpel, Cristina Kraemer; Brandão, Paulo E.; de Souza Filho, Antônio F.; de Souza, Robson F.; Ikuta, Cássia Y.; Ferreira Neto, José Soares; Camargo, Naila C. Soler; Heinemann, Marcos Bryan; Guimarães, Ana M. S. (Frontiers in Microbiology, 2017)
Mycobacterium bovis causes bovine tuberculosis and is the main organism responsible for zoonotic tuberculosis in humans. We performed the sequencing, assembly and annotation of a Brazilian strain of M. bovis named SP38, and performed comparative genomics of M. bovis genomes deposited in GenBank. Mycobacterium bovis SP38 has a traditional tuberculous mycobacterium genome of 4,347,648 bp, with 65.5% GC, and 4,216 genes. The majority of CDSs (2,805, 69.3%) have predictive function, while 1,206 (30.07%) are hypothetical. For comparative analysis, 31 M. bovis, 32 Mycobacterium bovis BCG, and 23 Mycobacterium tuberculosis genomes available in GenBank were selected. Mycobacterium bovis RDs (regions of difference) and Clonal Complexes (CC) were identified in silico. Genome dynamics of bacterial groups were analyzed by gene orthology and polymorphic sites identification. Mycobacterium bovis polymorphic sites were used to construct a phylogenetic tree. RD analyses resulted in the exclusion of three genomes, mistakenly annotated as virulent M. bovis. Mycobacterium bovis SP38 along with strain 35 represent the first report of CC European 2 in Brazil, whereas two other M. bovis strains failed to be classified within current CC. Results of M. bovis orthologous genes analysis suggest a process of genome remodeling through genomic decay and gene duplication. Quantification, pairwise comparisons and distribution analyses of polymorphic sites demonstrate greater genetic variability of M. tuberculosis when compared to M. bovis and M. bovis BCG (p≤0.05), indicating that currently defined M. tuberculosis lineages are more genetically diverse than M. bovis CC and animal-adapted MTC species. As expected, polymorphic sites annotation shows that M. bovis BCG are subjected to different evolutionary pressures when compared to virulent mycobacteria. Lastly, M. bovis phylogeny indicates that polymorphic sites may be used as markers of M. bovis lineages in association with CC. Our findings highlight the need to better understand host-pathogen co-evolution in genetically homogeneous and/or diverse host populations, considering the fact that M. bovis has a broader host range when compared to M. tuberculosis. Also, the identification of M. bovis genomes not classified within CC indicates that the diversity of M. bovis lineages may be larger than previously thought or that current classification should be reviewed.